Drug therapy, imaging, and other aspects of clinical management change after Alzheimer's biomarker testing in routine practice: Findings from the IMPACT‐AD BC study. (20th December 2022) - Yang, David; Best, John R.; Chambers, Colleen; Feldman, Howard H.; Pettersen, Jacqueline A; Henri‐Bhargava, Alexander; Lee, Philip E; Nygaard, Haakon B.; Funnell, Clark R; Foti, Dean J; Hsiung, Ging‐Yuek Robin; DeMarco, Mari L.
Abstract: Background: While previous studies have demonstrated the effect of Alzheimer's disease (AD) CSF testing in changing diagnosis, we lack an understanding of how this testing affects clinical management. Therefore, we assessed changes in clinical management associated with AD CSF biomarker testing when ordered as part of routine clinical management. Method: The 'Investigating the Impact of Alzheimer's Disease Diagnostics in British Columbia' (IMPACT‐AD BC) study (NCT05002699) is a longitudinal study examining the impact of AD CSF testing on clinical management, personal utility and health care economics in British Columbia, Canada. After AD CSF testing was ordered as part of routine care (where the clinical scenario met the appropriate use criteria), the patient and their physician were eligible to participate in the study. The primary outcome was the change in management (pre‐ v. post‐biomarker results) in a composite measure including 1) AD drug therapy, 2) other relevant drug therapy, 3) other diagnostic procedures, and 4) referral or counselling. Result: Participants (n = 129) had a median age of 63 (IQR:58‐68); 49% were female. Cognitive impairment at baseline consisted of 7% with subjective cognitive impairment, 53% with mild cognitive impairment, and 40% with dementia. CSF biomarker profiles were consistent with an amyloid‐beta pathology (i.e., A+) in 72% of cases. Changes in clinical management because of testing occurred in 83% of cases including: referrals and counseling (57%), imaging (47%) and other diagnostic procedures (e.g., neuropsychological testing) (42%), and use of AD drug therapies (40%). For those with a non‐AD pre‐biomarkers diagnosis, 42% were changed to AD post‐biomarkers; for those with an AD pre‐biomarkers diagnosis, 18% were changed to non‐AD post‐biomarkers. Conclusion: This study has revealed substantial changes in clinical management as a direct result of AD CSF biomarker testing in routine care. An understanding of the implications of biomarker testing will in turn help us: improve appropriate utilization, understand the broader impacts on persons living with dementia and on the health care system, and prepare for expanded use of this testing with the availability of disease‐modifying therapeutics.